(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Artificial composite materials are currently being produced in large quantities, they are diverse and they are widely used in the economy. There have been extensive theoretical and experimental studies of different types of components, developed the calculation methods of composites production with predefined properties.At the same time industry produces a lot of mineral and polymer waste, which are practically technogenic resources, but their use is currently at quite low levels. The paper examines the possibilities to use technogenic resources- mineral (such as ash and clay) and organic (polymers -PET containers) for producing qualitative composite materials. For this purpose theoretical analysis and calculations of the physical properties of components and process parameters that determine the operating characteristics of the composite material were carried out.Composite-forming process efficiency determinative parameters were analysed: adhesion, the specific surface energy, specific free surface, adsorption capacity and the degree of dispersion of the particles.The role of external factors in processing of composite were examined – temperature, concentration of components.The characteristics of prepared samples of composites showed the possibility to use these waste for the development of qualitative products for different purposes.